Optical Polarization Radiation of Relativistic Electrons in Conducting Targets; Russian Physics Journal; Vol. 45, iss. 9 - Naumenko G. A. Gennadiy Andreevich; Aleinik A. N. Aleksandr Nikonorovich; Aryshev A. S.; Kalinin B. N.; Karataev P. V.; Potylitsyn A. P. Alexander Petrovich; Saruev G. A. Gennady Alekseevich; Chefonov O. V.; Sharafutdinov A. N. (2002, 2002)
Title screen